2015
DOI: 10.1111/sms.12544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbohydrate dose and frequency on metabolism, gastrointestinal discomfort, and cross‐country skiing performance

Abstract: This study investigated carbohydrate ingestion of varied doses and frequencies during a simulated cross‐country skiing time trial. Ten men and three women (age: 30 ± 7 years; boldV bold˙ boldO 2 m a x : 59.6 ± 5.7 mL/kg/min) completed four, 30‐km classic technique roller skiing time trials on a treadmill. A 1:1 maltodextrin‐fructose carbohydrate solution was provided at high (2.4 g/min; HC) and moderate (1.2 g/min; MC) ingestion rates, each at high (six feeds; HF) and low (two feeds; LF) frequencies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
3
1
1
Order By: Relevance
“…Likewise, Trommellen and colleagues also showed that the combined ingestion of Glc and Fru (1.2 g/kg/h Glc plus 0.3 g/kg/h Fru or 0.9 g/kg/h Glc +0.6 g/kg/h Suc) did not further accelerate post-exercise synthesis of muscle glycogen, compared to ingestion of 1.5 g/kg/h of Glc alone [ 91 ]. Hence, these data clarify that the post exercise muscle glycogen regeneration rate is independent from the type and the length of ingested CHO; but the combined ingestion of Glc and Fru or Suc results in less gastrointestinal disturbance compared to Glc alone, due to a lower accumulation of CHO in the gastrointestinal tract, in line with previous studies [ 91 , 93 ].…”
Section: Functional Beverages Containing Chosupporting
confidence: 89%
“…Likewise, Trommellen and colleagues also showed that the combined ingestion of Glc and Fru (1.2 g/kg/h Glc plus 0.3 g/kg/h Fru or 0.9 g/kg/h Glc +0.6 g/kg/h Suc) did not further accelerate post-exercise synthesis of muscle glycogen, compared to ingestion of 1.5 g/kg/h of Glc alone [ 91 ]. Hence, these data clarify that the post exercise muscle glycogen regeneration rate is independent from the type and the length of ingested CHO; but the combined ingestion of Glc and Fru or Suc results in less gastrointestinal disturbance compared to Glc alone, due to a lower accumulation of CHO in the gastrointestinal tract, in line with previous studies [ 91 , 93 ].…”
Section: Functional Beverages Containing Chosupporting
confidence: 89%
“…While a self-paced treadmill of this type is uncommon it is not unique, with other research groups describing similar systems within laboratory settings (Stöggl et al, 2007; Losnegard et al, 2012). With reliable performance data, a range of novel laboratory-based studies are possible using running or cross-country roller-skiing, as opposed to the more common mode of cycling, whereby pacing and intervention strategies may be examined in relation to maximal performance (Andersson et al, 2016; Stocks et al, 2016; Watkins et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…More rapid digestion and absorption is also a likely cause of the lower gastrointestinal distress observed with high ingestion rates of isocaloric glucose–fructose mixtures over glucose alone. Lower gastrointestinal distress could, in part, account for some of the performance benefits seen with glucose–fructose co-ingestion [16,81]. The high rates of carbohydrate absorption with glucose–fructose co-ingestion also raise the possibility of enhancing the rate of recovery of endogenous carbohydrate stores post-exercise.…”
Section: Physiological Rationale For Glucose–fructose Co-ingestionmentioning
confidence: 99%